Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Join Brainly to access

this expert answer

SEE EXPERT ANSWER

To see the **expert** answer you'll need to create a **free** account at **Brainly**

rearrange the equation of 2x-y=6 into terms of y first.

so y=-2x+6?

y=2x+6

ok

now, solve both equations

1) y=2x-6
2) y=-3x+19

tell me what you get for the x value afterwards.

how though?

do you know how to solve for both equations?

no

okok, let me explain sonja, it's sonja right?

yes

|dw:1350442906070:dw|

y-y= 0
2x--3x becomes 2x+3x=5x
-6-19=-25
0=5x-25
5x-25=0
5x=25
x=25/5
x=5